Safety of biological preparations. Report 1. Terminology and classification issues - A. A. Soldatov; Zh. I. Avdeeva; Yu. V. Olefir; V. A. Merkulov; V. P. Bondarev (Биопрепараты: Профилактика, диагностика, лечение, 2018)
Adverse drug reactions (ADR) are injuries caused by taking a medication. For the purpose of an objective analysis of the reasons and mechanisms of ADR, with a view to developing the methods for their relief and prevention, one should use standard criteria for the characterization of ADR. Typically, the description of ADR includes information about the damaged organ or tissue and the frequency of ADR occurrence. To characterize ADRs caused by low molecular weight chemicals proposed, an A/B classification and its modifications have been proposed, based on the possible mechanisms of ADR. Biological preparations differ from chemicals by a number of characteristics, including the mechanism of action. Considering the nature of biological/biotechnological preparations, several types of ADR classifications, related to the mentioned drug group, have been suggested. The most popular classification for ADR related to biological preparations have been suggested by W. J. Pichler. It is based on the involvement of immunological mechanisms in ADR occurrence. This classification divides ADR related to biologicals into 5 types: type α (reactions caused by high level of cytokines), type β (hypersensitivity reaction), type γ (reactions caused by the imbalance of immune factors), type δ (cross-reactivity reactions) and type ε (reactions caused by non-immunological mechanisms). The mentioned classification method has certain disadvantages: it does not cover all biological preparations, but only drugs, containing cytokines, hormones and monoclonal antibodies preparations; and it does not consider ADR occurring without immune mechanisms (such as increased blood pressure when administering preparations of recombinant erythropoietins).